The Power of Figurative Language in Game Storytelling: A Case Study of Mouthwashing - Ridwan, Andi Shafiyah Salsabila; Hasbi, Muh. (State University of Makassar, 2025)
Video games, as a 21st-century storytelling medium, integrate interactive elements and visual artistry to engage players on a personal level. This study aims to explore the role of figurative language using in the psychological horror game Mouthwashing by analyzing how literary devices like hyperbole, irony, metaphor, and symbolism enrich its narrative and thematic depth. This study used a descriptive qualitative research design where the data was obtained from the game’s non-linear storytelling and symbolic dialogue. Qualitative discourse analysis was employed and centered on the figurative language that characterizes the game Mouthwashing to criticize societal issues such as corporate neglect and personal despair, while enhancing emotional immersion and horror tension. The finding demonstrates how figurative language is integral to shaping character development, conveying complex themes, and engaging players in reflective experiences. The study also reveals that figurative language transforms Mouthwashing game into a sophisticated narrative art form, illustrating the evolving role of video games as platforms for artistic and social expression. Keywords: Figurative Language, Linguistics, Mputhwashing, Video Game